Evaluation of the potential of solar energy utilization in Famagusta, Cyprus. (February 2018) - Ouria, Mahmoud; Sevinc, Harun
Abstract: This paper investigates the use of solar energy in urban areas as exemplified by Famagusta in Cyprus. All the climatic and geographic factors were analyzed to compute the solar energy potential for Famagusta City. Next, the solar energy utilization potential in the Social Housing Complex (SHC) district of Famagusta was investigated in detail. The effective parameters of solar energy, including climatic factors, radiation types, geographic parameters, orientation techniques, height to width ratio (H/W) and landscape analysis, were evaluated based on Famagusta using DuffieBeckman and Stephenson's cousin methods. The rate of irradiation solar energy was analyzed for horizontal, vertical and tilted surfaces of blocks and routes in the SHC in Famagusta City using Ladybug for Rhino and MS Excel software programs. The results of this study showed that the district landscape is very poor from a solar energy point of view. While there is a great source of solar energy producing extreme heat, the solar energy is not utilized properly, as the district is not walkable, especially in the afternoons. It is recommended that pedestrians be helped by adding hardwood trees, by using solar panels to generate renewable power for lightning, and by using permeable materials for pavements.